0
$\begingroup$

If $S\equiv \sin\theta+2\sin2\theta+3\sin3\theta+......+n\sin n\theta$ and $C\equiv \cos\theta+2\cos2\theta+3\cos3\theta+......+n\cos n\theta$,prove that

$4\sin^2\frac{\theta}{2}.S=(n+1)\sin n\theta-n \sin (n+1)\theta$,

and $4\sin^2\frac{\theta}{2}.C=-1+(n+1)\cos n\theta-n \cos (n+1)\theta$

My try:$4\sin^2\frac{\theta}{2}.S$
$=2(1-\cos \theta)[\sin\theta+2\sin2\theta+3\sin3\theta+......+n\sin n\theta]$
$=2[\sin\theta+2\sin2\theta+3\sin3\theta+......+n\sin n\theta-\cos\theta\sin\theta-2\cos\theta\sin2\theta+.....-n\cos\theta\sin n\theta]$

but it is not getting further simplified.Please help me.

$\endgroup$
1
$\begingroup$

HINT:

$$2r(1-\cos y)\cdot\sin ry=2r\sin ry-r(2\sin ry\cos y)$$ $$=2r\sin ry-r\{\sin(r+1)y-\sin(r-1)y\}$$

$$=-r\{\sin(r+1)y-\sin ry\}+r\{\sin ry-\sin(r-1)y\}$$

Do you know about Telescoping Series?

Set $r=1,2,3,\cdots,n-1,n$ and add

Similarly, $$2r(1-\cos y)\cdot\cos ry=2r\cos ry-r(2\cos ry\cos y)=?$$

$\endgroup$
1
$\begingroup$

HINT:

Using Euler's formula, $$S_n=C+iS=\sum_{r=1}^n re^{ir\theta}$$

Now using Arithmetic-Geometric Series, $$S_n=\dfrac{1-(n+1)e^{in\theta}+ne^{i(n+1)\theta}}{(1-e^{i\theta})^2}$$

Simplify and equate the real & the imaginary parts.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.